ETIKA KOMUNIKASI DALAM PERSFEKTIF ISLAM - Muslimah Muslimah (Lembaga penelitian dan pengabdian kepada Masyarakat, 2016)
One of the privileges granted by the Almighty God to man is the ability to communicate. This capability greatly assist people in meeting their needs effectively, and make it easier to communicate with each other. In addition, good communication skills and the right can be a way to deliver a person to success and will bring benefit to others. Conversely, the communication can also be a trigger kemudaratan, especially if someone is wrong in communicating or disturb people.The concept of communication is not only concerned with the problem of how to speak good but also the ethics of speech. Since entering the reform era, the people of Indonesia are in a independent atmosphere, free to talk about anything, to anyone, in any way. The Quran calls the communication as one of human nature. To find out how humans seharusya communicate. The Qur'an gives the keyword (keyconcept) yag associated with it. Al-Syaukani, for example, define the keyword al-bayan as the ability to communicate. In addition, the keywords used for communication Qur'an is al-qaul.This paper rests on the idea that every Muslim should be guided by the Qur'an in exploring life on earth. Communicating is an activity that can not be separated from human life. So that everyone is able to communicate properly and bring the benefit then he should be guided by the ethics of communication as outlined in the Qur an.The command said in the Qur'an and Hadith become an indication obligatory for Muslims to apply the nature of honesty and true are the words of the Qur'an concept known as qaulan sadidan.